2015
DOI: 10.2174/1871527315666151111124729
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Exercise: Effects on Gut Miccrobiota and Depression

Abstract: Microbiota is a set of microorganisms resident in gut ecosystem that reacts to psychological stressful stimuli, and is involved in depressed or anxious status in both animals and human being. Interestingly, a series of studies have shown the effects of physical exercise on gut microbiota dynamics, suggesting that gut microbiota regulation might act as one mediator for the effects of exercise on the brain. Recent studies found that gut microbiota dynamics are also regulated by metabolism changes, such as throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Yuan et al found that physical exercise modulated different population of gut bacteria or rich diet, and alleviated gut syndromes to toxin intake. Gut microbiota could as well contribute to the beneficial effects of exercise on cognition and emotion, either directly through serotonin signaling or indirectly by modulating metabolism and exercise performance [69]. Similarly, we found that resistance training significantly reverted the level of trimethylamine-N-oxide, indicating that it has a regulatory effect on the intestinal flora metabolism in depressed rats.…”
Section: Intestinal Microbial Metabolismsupporting
confidence: 60%
“…Yuan et al found that physical exercise modulated different population of gut bacteria or rich diet, and alleviated gut syndromes to toxin intake. Gut microbiota could as well contribute to the beneficial effects of exercise on cognition and emotion, either directly through serotonin signaling or indirectly by modulating metabolism and exercise performance [69]. Similarly, we found that resistance training significantly reverted the level of trimethylamine-N-oxide, indicating that it has a regulatory effect on the intestinal flora metabolism in depressed rats.…”
Section: Intestinal Microbial Metabolismsupporting
confidence: 60%
“…It is generally recognized that traditional antidepressant therapies alleviate mental and brain abnormalities and treat depression. But the latest research has found that traditional therapies not only regulate the brain but also influence gut microbiota; their antidepressant effects are probably partly related with the regulation of the microbiota–gut–brain axis [ 16 , 149 , 150 ].…”
Section: The Latest Research Progress Of Depression: the Microbiotmentioning
confidence: 99%
“…Other therapies also changed the gut microbiota. Except the dietotherapy mentioned above, exercise therapy probably improves depression via the regulation of gut microbiota and the microbiota–gut–brain axis; a poor sedentary life style characterized by a lack of exercises increases the incidence of depression, while getting enough exercise alleviates depression [ 150 , 151 ].…”
Section: The Latest Research Progress Of Depression: the Microbiotmentioning
confidence: 99%
“…Evidence suggests that aerobic exercise triggers diversity and abundance of genera from the Firmicutes phylum, with possible linkage with effects of exercise on the gut and brain [107]. What is undeniable is that synergic effects of microbiota with exercise on cognition and emotion play crucial roles in serotonin signaling and metabolism in general [285].…”
Section: Exercisementioning
confidence: 99%